APLIKASI PRESENSI SANTRI MENGGUNAKAN GOOGLE APPSHEET BERBASIS ANDROID: Studi Kasus pada Rumah Yatim dan Tahfidz Qur’an Madani - Siti Zulaiha; M. Syafiuddin Usman (Melati Institute, 2023)
The attendance system is very important for an educational institution to know the attendance of students. The development of the attendance system has now developed with the advancement of supporting technology such as computers and android smartphones. The technology made to do attendance is to use the platform provided by Google, namely AppSheet. This Google AppSheet is a platform that can be used to create applications or systems without using code or programming languages. In this research, the system development method used is the waterfall method. With the online attendance system created using Google AppSheet, students and student administrators at the Madani Quran Orphanage and Tahfidz will be helped and further streamline the time of teaching and learning activities carried out by students every day.